(untitled) - Greig, Alastair (Cambridge, UK, 2003)
This text seeks to analyse and explain inequality, challenging traditional conceptions and providing a new critical perspective. The authors provide a comprehensive historical account of inequality, and show how that account no longer adequately explains the new and different forms of inequality experienced in recent decades. As society has changed, they argue, new forms of inequality have emerged, conditioning the subject's very experience of identity, embodiment and politics. The book is at once a critical overview of contemporary inequality and a thorough-going textbook suitable for undergraduates.
Keywords: Equality,Australia,Bình đẳng,Nước Úc; Social conditions,Khía cạnh xã hội; 21st century,Thế kỷ 21; Australia,Úc